2018
DOI: 10.1016/j.jobe.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural response of modular buildings – An overview

Abstract: Prefabrication by off-site manufacturing leads to a reduced overall construction schedule, improved quality, and reduced resource wastage. Modular building is therefore increasingly popular and promoted. With the recent promotion a number of relevant studies have been completed, however, a review of the design, construction, and performance of modular buildings under different loading conditions is lacking. This paper presents a state-of-the-art review of modular building structures. First, structural forms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(132 citation statements)
references
References 79 publications
1
121
0
10
Order By: Relevance
“…loading has been evaluated by many researchers from around the world and incorporated into the design of a range of approaches. However, structural performance data of prefabricated building structures is limited, as little detail of engineering research and few case studies have been published [3,42,43]. The structural design approach should ensure the stability of the building structure under these natural and manmade loads, transferring such loads to the foundation through their structural elements, non-structural elements and inter-component connections.…”
Section: Structural Performance Of Prefabricated Building Systemsmentioning
confidence: 99%
“…loading has been evaluated by many researchers from around the world and incorporated into the design of a range of approaches. However, structural performance data of prefabricated building structures is limited, as little detail of engineering research and few case studies have been published [3,42,43]. The structural design approach should ensure the stability of the building structure under these natural and manmade loads, transferring such loads to the foundation through their structural elements, non-structural elements and inter-component connections.…”
Section: Structural Performance Of Prefabricated Building Systemsmentioning
confidence: 99%
“…Reinforced concrete slabs and partition walls are usually integrated in the steel module to ensure good acoustic and thermal insulation, providing a complete building system for modular steel construction (MSC). It has been demonstrated that MSC can fully exploit the advantages of modular construction, especially with regard to speed of construction [ 10 ]. In a very recent example, a post-disaster hospital that could accommodate 1000 patients was successfully built in just 10 days by employing MSC in Wuhan, China, aiding in the fight against the virus COVID-19 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, more than 85% of the architecture is prefabricated. With most parts completed in the factory and fewer at the construction site, modular buildings have many advantages, such as flexible designs, low carbon use, energy savings, high efficiency in manufacturing, fast construction, fine quality, low cost, safety in construction, reduced sensitivity to the environment and no need for secondary decoration [4][5][6]. To overcome the above difficulties, taking advantage of the fast construction of module buildings and achieving the goal of complete decoration in the factory, this paper proposes a new type of modular connection which can connect eight modules as a whole at the central column on the construction site.…”
Section: Introductionmentioning
confidence: 99%